2015
DOI: 10.1007/s12134-015-0432-2
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Return Intentions and Home Investment: the Case of Ghanaian Migrants in Southern Europe

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The high living standards and earnings in most destination countries shape the expectation of most migrants about their home countries. 24 It has been argued that most migrants prior to their return invest at home or return along with sufficient savings or pensions to avoid the risk of reverting to premigration living standards. 25 Agyeman and Garcia go on to report that in recent times, most countries of return have introduced new policies and formal arrangements with host countries, which allow return migrants to continue to access services and entitlements earned in the host country (like social security and employment pension arrangements) after they have returned to their country of origin.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The high living standards and earnings in most destination countries shape the expectation of most migrants about their home countries. 24 It has been argued that most migrants prior to their return invest at home or return along with sufficient savings or pensions to avoid the risk of reverting to premigration living standards. 25 Agyeman and Garcia go on to report that in recent times, most countries of return have introduced new policies and formal arrangements with host countries, which allow return migrants to continue to access services and entitlements earned in the host country (like social security and employment pension arrangements) after they have returned to their country of origin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…133 Building national and local capacities also "entails working with both the private sector and recruitment agencies [in the provision of services] to support the economic reintegration through employment." 134 Structural interventions are necessary for creating the right institutional environment for successful reintegration. According to the IOM, structural interventions are necessary because they "aim to strengthen national capacities to provide reintegration services to returning migrants through technical support and tools,…”
Section: Structural Initiativesmentioning
confidence: 99%
“…remittances (Dustmann and Mestres (2010a); Delpierre and Verheyden (2014)), asset holdings in the origin and destination countries (Dustmann andMestres (2010b), Chabé-Ferret et al (2018)), and entrepreneurial investments in the home country (Ammassari (2004); Akwasi Agyeman and Fernández Garcia (2016)).…”
Section: Related Literaturementioning
confidence: 99%
“…Even though the two strategies are different, their ultimate goals, however, are to reduce the propensity to migrate from sub-Saharan Africa to Spain and to the European Union, ensure that unwanted African migrants do not arrive in their territory, remove those who enter or stay in Spanish territory without authorization, and encourage voluntary return of those who have legally settled in Spain (Agyeman, 2011;Agyeman and Fernandez Garcia, 2016). MARITIME BORDER CONTROL SYSTEMS Alscher (2005) observed that during the period between 2000 and 2004 when Spain's conservative Popular Party (PP) won an absolute majority in parliament, the fight against illegal migration became the central issue of immigration policy.…”
Section: Stemming African Migration To Spainmentioning
confidence: 99%